2019
DOI: 10.37358/rc.19.8.7452
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Polyphenols Isolated from Branches of Prunus spinosa L. Species

Abstract: The aim of this study was to investigate the crude extracts isolated from branches of Prunus spinosa L. (Rosaceae), in order to quantify polyphenols and tannins using instrumental methods (UV-Vis spectrometry and HPTLC densitometry). The qualitative analysis on biomass revealed the presence of valuable compounds such as polyphenols, flavonoids and tannins. HPTLC fingerprinting of crude methanol extract showed several peaks, with different Rf values, corresponding to phytocompounds such as chlorogenic acid (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The study conducted by Ciuperca et al in 2019 [69] focused on extracting polyphenols from the branches of P. spinosa L. in Bacău County, Romania. The study found a polyphenol content of 2.97 ± 0.059 mg gallic acid equivalent/g of dry weight, as well as a tannin content of 0.90 ± 0.033 g tannic acid equivalent/g of dry weight.…”
Section: The Polyphenol Composition In Various Parts Of the P Spinosa...mentioning
confidence: 99%
“…The study conducted by Ciuperca et al in 2019 [69] focused on extracting polyphenols from the branches of P. spinosa L. in Bacău County, Romania. The study found a polyphenol content of 2.97 ± 0.059 mg gallic acid equivalent/g of dry weight, as well as a tannin content of 0.90 ± 0.033 g tannic acid equivalent/g of dry weight.…”
Section: The Polyphenol Composition In Various Parts Of the P Spinosa...mentioning
confidence: 99%
“…It is a dense and spiny shrub growing to 1-2 m on the fringe of forests, clearings and pastures. Blackthorn is an abundant source of bioactive polyphenols, such as phenolic acids (chlorogenic acid, neochlorogenic acid, caffeic acid and protocatechuic acid), flavonoids, anthocyanins, as well as condensed tannins [25][26][27][28] with proved antioxidant effects [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The solvent moves into the vegetal matrix and solubilize the compounds with similar polarity. There are well known several conventional extraction techniques as well as some nonconventional, developed more recently [14][15][16]. The conventional techniques (solid-liquid extraction at room temperature or using heat reflux) use organic solvents (hexane, acetone, methanol, ethanol etc.)…”
Section: Introductionmentioning
confidence: 99%